Unpacking Living Originalism and Living Constitutionalism in the Constitutional Contexts of India and Pakistan - Ali, Muhammad Imran (Faculty of Law, University of Jember, Indonesia, 2024)
Originalism versus living constitutionalism is widely regarded as one of the most contentious current battles over constitutional interpretation. Originalism as a theory seeks to instill original understanding of constitutional provisions in a contemporary constitutional premise by opposing the broad interpretive practice known as living constitutionalism, which prioritizes modern understandings. Originalism theory is an interpretation theory whereas living constitutional theory is a construction theory. Although interpretation is only one activity, it is insufficient to make the Constitution functional. Construction, which involves putting the principles into practice and laying out the institutions that will carry out constitutional functions, is another activity that leads to the establishment of constitutional provisions. When it comes to living Originalism, however, it is the interpretation of provisions that is done to determine the true and actual meaning. It advocates both forms, namely originalism and living constitutionalism which appear to complement one another. The Indian Constitution is a blend of rigidity and flexibility and thus supports living originalism, whereas emerging trends in Pakistani courts favour living constitutionalism. This article analyzes the living originalism approach within the Constitution of India and the living constitutionalism method inside the Constitution of Pakistan. It explores the nuanced views on constitutional commitments within these frameworks, elucidating the impact of interpretative techniques on prison discourse, judicial decisions, and standard constitutional tendencies in both South Asian countries. By delving into these procedures, this has a look at goals to provide a complete knowledge of ways they make a contribution to the evolving nature of constitutional interpretation and governance in India and Pakistan. This article adopts a literature review method.